Asia in global governance: A case for decentralized institutions - Masahiro Kawai; Peter A. Petri; Elif Sisli-Ciamarra (Asian Development Bank Institute (ADBI), 2009)
The global economic crisis refocused attention on the governance of international economic institutions (IEIs). This study uses the analytical framework of club theory to highlight structural obstacles to reform in international macroeconomic management, development finance, trade, and financial stability. The authors argue that reforms currently being discussed - for example, in voting power in the International Monetary Fund and the World Bank - are important, but not sufficient to make IEIs adaptable to the demands of a rapidly changing world economy. The authors propose transforming IEIs by shifting more decisions from the global to sub-global level. Partially decentralized decision making already exists in some policy areas (for example in regional development banks) and could expand and improve the provision of international public goods.
Keywords: F02; F13; F33; F42; 330